PENGEMBANGAN MODEL PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN-WRITE UNTUK MENDAPATKAN GAMBARAN KUANTITAS MISKONSEPSI SISWA SMA MATERI SUHU DAN KALOR - Supriyati, Supriyati (Jurnal Pendidikan Fisika, 2015)
Application of learning models POEW done to minimize the quantity of misconceptions experienced by students. The research was conducted by applying the POEW model of the experimental class and POE model of the control class. A method use quasi-experimental by design âRandomized Control Group Pretest-Posttest Designâ implemented in X class one of high school at the city Cimahi in 2012/2013. Research results show that the description of misconception experienced by students in the experimental class lower than the control class. Responses of students to learn with the application of this POEW generally positive.